Identification of Landslide Prone Zone Slide Plane Using 2D Resistivity Geoelectric Method in Samboja Region East Kalimantan - Silalahi, Mawar Dini Erena; Prasetya, Anggara Putra; Puspa, Rahma; Santoso, Budy (Universitas Padjadjaran, 2025)
This study aims to investigate subsurface conditions to identify ground movement and landslide potential in Samboja District, Kutai Kartanegara Regency, East Kalimantan. To delineate slip surfaces in landslide-prone areas, the research employs the 2D electrical resistivity method using a dipole-dipole electrode configuration. Geoelectrical measurements were conducted along four survey lines based on resistivity values to determine subsurface characteristics indicative of potential slip surfaces. The results show that each survey line has distinct soil and rock properties, influencing the type of landslide that may occur. SBJ01 was measured on an outcrop and used as calibration data for other lines. SBJ02 is susceptible to soil creep, SBJ03 is at risk of translational landslides, while SBJ10 indicates debris flow. The primary factors contributing to landslides in the study area include rainfall infiltration, which increases pore water pressure, and lithological conditions that form weak slip surfaces. This study confirms that the 2D electrical resistivity method is effective in identifying slip surfaces in landslide-prone areas and serves as a valuable reference for disaster mitigation efforts.